2019
DOI: 10.18388/abp.2019_2844
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of USP18 in physiology and pathophysiology

Abstract: Ubiquitin-specific peptidase 18 (USP18) is a multifunctional protein and its roles are still being investigated. This enzyme removes ubiquitin-like molecules from their substrates and the only known interferon-stimulated gene 15 (ISG15) specific protease. Apart from its enzymatic function, it also inhibits interferon type I and III signalling pathways. USP18 is known to regulate multiple processes, such as: cell cycle, cell signalling and response to viral and bacterial infections. Moreover, it contributes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Ubiquitin‐specific peptidase 18 (USP18) is considered a critical multifunctional deubiquitinase that moderates the stability of key proteins to contribute to the carcinogenesis process. [ 43 , 44 ] Recently, PD‐1/PD‐L1‐targeting immune checkpoint inhibitors (ICIs) have been proven to be promising treatment modalities in bladder cancer. [ 45 , 46 ] Our study demonstrated that USP18 downregulation caused by BCCE4 [A] could decrease the protein stability of PD‐L1, attenuate the PD‐L1/PD‐1 interaction and sensitize bladder cancer cells to T‐cell‐mediated killing.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin‐specific peptidase 18 (USP18) is considered a critical multifunctional deubiquitinase that moderates the stability of key proteins to contribute to the carcinogenesis process. [ 43 , 44 ] Recently, PD‐1/PD‐L1‐targeting immune checkpoint inhibitors (ICIs) have been proven to be promising treatment modalities in bladder cancer. [ 45 , 46 ] Our study demonstrated that USP18 downregulation caused by BCCE4 [A] could decrease the protein stability of PD‐L1, attenuate the PD‐L1/PD‐1 interaction and sensitize bladder cancer cells to T‐cell‐mediated killing.…”
Section: Discussionmentioning
confidence: 99%
“…This process can be reversed by deubiquitinase enzymes, which are central to its regulation. Moreover, ubiquitin-like proteins also participate in post-translational modifications via mechanisms similar to ubiquitination (9,10). Ubiquitin-specific peptidase 18 (USP18), also known as ISG43, UBP43, and PTORCH2, is a member of the USP family that deubiquitinates proteins.…”
Section: Generalities Of Ubiquitin Specific Peptidase 18 (Usp18)mentioning
confidence: 99%
“…Ubiquitin-specific peptidase 18 (USP18) is a multifunctional protein 20 . Originally, USP18 is identified as the deISGlase and removes interferon-stimulated gene 15 (ISG15) from the substrate proteins 21 .…”
Section: Introductionmentioning
confidence: 99%